심장수술 환자에서 좌심방압의 평가를 위한 폐중심정맥압 , 이완기 폐동맥압 및 폐모세혈관쐐기압의 비교 - 김용락; Yong Lak Kim; 조대현; Dae Hyun Jo; 김용주; Yong Joo Kim (Korean journal of anesthesiology, 1996)
Background: To evaluate the left heart function, left atrial pressure(LAP) has been monitored directly via LA catheter and indirectly via Swan-Ganz catheter. But indirect pressure monitor cannot often reflect the LAP precisely. We compared the LAP via LA catheter with central venous pressure(CVP), diastolic pulmonary artery pressure(DPAP) and pulmonary capillary wedge pressure(PCWP) by Swan-Ganz catheter. Methods: Eleven cardiac-surgical patients whose LAP measurements were needed for clinical management were the subjects of this study. The CVP, DPAP and PCWP by Swan-Ganz catheter, and LAP were measured just after cardiopulmonary bypass, just after sternal closure, after 6 hours and 18 hours from the end of operation. And we divided them into two groups which consisted below 35 mmHg(group I) and over 35 mmHg(group II) of systolic pulmonary artery pressure(SPAP), and compared two groups. Results: In group I, the LAP, CVP, DPAP and PCWP was 11.7±3.9 mmHg, 10.5±3.9 mmHg, 12.5±5.1 mmHg and 12.5±4.4 mmHg respectively, and correlation coefficiency of LAP with CVP, DPAP and PCWP was 0.7478, 0.7128 and 0.9002 respectively(p<0.05). In the group II, the LAP, CVP, DPAP and PCWP was 16.5±3.2 mmHg, 12.8±2.9 mmHg, 23.4±3.8 mmHg and 20.8±4.7 mmHg respectively and there was no correlation between LAP, CVP, DPAP and PCWP. Conclusion: The Swan-Ganz catheterization for the estimation of LAP is useful in the patients without pulmonary hypertension, but in the patient with pulmonary hypertension, CVP, DPAP and PCWP do not reflect the LAP.(Korean J Anesthesiol 1996; 30: 172~177)